Research on Integrated Learning upon Enhancing Cognitive Activity in Primary School - Zhekibayeva, Botakoz; Kalimova, Assemgul; Sarsekeyeva, Zhanar; Ossipova, Serafima; Zhukenova, Gulpara (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The study aims to identify the possibility of using a set of methods that a future teacher can apply upon working with schoolchildren, and value-based attitudes, which subsequently develop the students’ desire to learn. Background: The model for preparing the teaching staff for work at school presupposes the presence of not only the already approved tools for assessing the quality of education but also the development of teaching principles. For this purpose, the structure of integrated education is applied, which forms the possibility of holistic comprehension of the surrounding world for schoolchildren and the use of technologies for sustainable education on the part of the teacher. Method: To develop the above methods and attitudes, a pedagogical experiment was performed. In order to study the level of cognitive activity of young schoolchildren, experimental work based on the gymnasium was conducted. Results: The authors demonstrate that integrated learning can be achieved only if the younger schoolchildren are prepared and discovered their individual way of thinking and desire for knowledge. The study identifies the possibility of using a set of methods that a future teacher can apply upon working with schoolchildren and value-based attitudes, which subsequently develop the students’ desire to learn. Conclusion: The authors have concluded that the use of the integrated learning methodology allows to expand pedagogical techniques and use them natively in high school